(3CegGJ GdChdGO SDGd eMeO Hf SYO hLhGH GdgGOi Edi GdMbs - (3jMji Hf GdMSjf Hf GdbGSe Hf EHQGgje GdMSfj GdYdhqj GdQSj, GdeYQha H GdgGOj pEdi GdnMqb, J (B298 (3g` s
(3ChdgG (B:s
(3Yf QLd cGfJ dg RhLI eedhcI Ke GTJQGgG RhLgG ? s
(3BNQgG (B:s
(3aGage eG TQMJ dc ai Pdc hejRg HdHc s
(3hgh LhGH SDGd ai Mce CegGJ GdChdGO ef eMeO Hf SYjO ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs